BK polyomavirus genotypes in renal transplant recipients in the United States: A meta-analysis - Charat Thongprayoon (2020)
© 2019 Chinese Cochrane Center, West China Hospital of Sichuan University and John Wiley & Sons Australia, Ltd Background: In the United States, increasing ethnic diversity has been apparent. However, the epidemiology and trends of BKV genotypes remain unclear. This meta-analysis was conducted with the aim to assess the prevalence of BKV genotypes among kidney transplant (KTx) recipients in the United States. Methods: A comprehensive literature review was conducted through October 2018 utilizing MEDLINE, Embase, and Cochrane Database to identify studies that reported the prevalence of BKV subtypes and/or subgroups in KTx recipients in the United States. Pooled prevalence rates were combined using random effects, generic inverse variance method. The protocol for this study is registered with PROSPERO (no. CRD42019134582). Results: A total of eight observational studies with a total of 193 samples (urine, blood, and kidney tissues) from 188 BKV-infected KTX recipients were enrolled. Overall, the pooled estimated prevalence rates of BKV subtypes were 72.2% (95% confidence of interval [CI]: 62.7-80.0%) for subtype I, 6.8% (95% CI: 2.5-16.9%) for subtype II, 8.3% (95% CI: 4.4-15.1%) for subtype III, and 16.1% (95% CI: 10.4-24.2%) for subtype IV, respectively. While metaregression analysis demonstrated a significant positive correlation between year of study and the prevalence of BKV subtype I (slopes = +0.1023, P =.01), there were no significant correlations between year of study and percentages of BKV subtype II-IV (P >.05). Among KTx recipients with BKV subtype I, the pooled estimated percentages of BKV subgroups were 22.4% (95% CI: 13.7-34.5%) for subgroup Ia, 30.6% (95% CI: 17.7-47.5%) for subgroup Ib1, 47.7% (95% CI: 35.8-59.9%) for subgroup Ib2, and 4.1% (95% CI:1.2-13.3%) for subgroup Ic, respectively. Conclusion: BKV subtype I is the most prevalent subtype among KTx recipients in the United States and its prevalence seems to increasing overtime. Subgroup Ib2 is the most common subgroup among BKV subtype I.